2018
DOI: 10.1371/journal.pone.0208426
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota control acute arterial inflammation and neointimal hyperplasia development after arterial injury

Abstract: BackgroundThe microbiome has a functional role in a number of inflammatory processes and disease states. While neointimal hyperplasia development has been linked to inflammation, a direct role of the microbiota in neointimal hyperplasia has not yet been established. Germ-free (GF) mice are an invaluable model for studying causative links between commensal organisms and the host. We hypothesized that GF mice would exhibit altered neointimal hyperplasia following carotid ligation compared to conventionally raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…An influence of the microbiome on the development of atherosclerosis and restenosis has also been suggested in recent studies. A comparison of aseptic and conventionally raised mice showed that the latter had more advanced neointimal formation, which was probably related to changes in the kinetics of acute inflammation and wound healing ( 33 ). Intestinal dysbiosis also appeared to contribute to the development of atherosclerosis by modulating inflammatory events caused by differences in the production of microbial metabolites ( 34 , 35 ).…”
Section: Pathophysiology Of Restenosismentioning
confidence: 99%
“…An influence of the microbiome on the development of atherosclerosis and restenosis has also been suggested in recent studies. A comparison of aseptic and conventionally raised mice showed that the latter had more advanced neointimal formation, which was probably related to changes in the kinetics of acute inflammation and wound healing ( 33 ). Intestinal dysbiosis also appeared to contribute to the development of atherosclerosis by modulating inflammatory events caused by differences in the production of microbial metabolites ( 34 , 35 ).…”
Section: Pathophysiology Of Restenosismentioning
confidence: 99%
“…During the last decade, an increasing number of studies has provided a wealth of association-based [1][2][3] and causal evidence, 1,[4][5][6][7] linking the microbiota and specific bacterial community members [8][9][10] to the development of atherosclerotic lesions and cardiovascular disease (CVD) (for overview see Table 1). 11 The gut microbiota has been recognized as an environmental factor that influences endothelial cell functions and contributes to vascular inflammatory phenotypes, [12][13][14] fostering arterial thrombosis through various prothrombotic mechanisms. [15][16][17][18] While experiments with germ-free (GF) apolipoprotein E (Apoe)deficient mouse models at chow diet conditions have repeatedly shown a protective role of the microbiota in atherogenesis, 4,6 it remains controversial how HFD and different feeding regimens affect atherosclerotic lesion development in mouse atherosclerosis models under GF housing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has revealed the association between gut dysbiosis and arterial remodeling. Compared to conventional mice, germ-free mice show attenuated neointimal hyperplasia development and reduced local inflammation in arteries after carotid ligation (21). Concomitantly, CAD patients with instent hyperplasia and stenosis showed significant alteration in gut microbiota diversity and composition compared to CAD patients with in-stent patency.…”
Section: Discussionmentioning
confidence: 97%